Effect of Hot-Air and Freeze-Drying on the Quality Attributes of Dried Pomegranate (Punica granatum L.) Arils During Long-Term Cold Storage of Whole Fruit - Adegoke Olusesan Adetoro; Umezuruike Linus Opara; Olaniyi Amos Fawole (Agriculture, 2020)
This study investigated the effect of hot-air and freeze-drying on the physicochemical, phytochemical and antioxidant capacity of dried pomegranate arils during long-term cold storage (7 ± 0.3 °C, with 92 ± 3% relative humidity) of whole fruit over a single experiment. Extracted arils were processed at monthly intervals during 12 weeks of cold storage of whole fruit. After the 12-week storage period, hot-air and freeze-dried arils showed the least (3.02) and highest (23.6) total colour difference (TCD), respectively. Hot-air dried arils also contained 46% more total soluble solids (TSS) than freeze-dried arils. During the storage of pomegranate fruit, total phenolic content (TPC) steadily increased from 20.9 to 23.9 mg GAE/100 mL and total anthocyanin content (TAC) increased from 6.91 to 8.77 mg C3gE /100 mL. Similarly, an increase in TPC and TAC were observed for hot-air (9.3%; 13%) and freeze-dried arils (5%; 5%), respectively. However, the radical scavenging activity (RSA) reduced by 8.5 and 17.4% for hot-air and freeze-dried arils, respectively, after 12 weeks of cold storage. Overall, the parameters such as colour, TPC and TAC as well as the lower degradation in RSA stability during storage showed distinct differences in quality when using the freeze-drying method, which is, therefore, recommended.